Budget Consolidation : Short-Term Pain and Long-Term Gain - Laxton, Douglas (IMF Working Papers; Working Paper ;, 2010)
The paper evaluates the costs and benefits of fiscal consolidation using simulations based on the IMFs global DSGE model GIMF. Over the longer run, well-targeted permanent reductions in budget deficits lead to a considerable increase in both the growth rate and the level of output. The gains may be enhanced by shifting some of the tax burden from incomes to consumption. In the short run, credibility plays a crucial role in determining the size of initial output loses. Global current account imbalances would be significantly reduced if budget consolidation was larger in countries with current account deficits.